2014
DOI: 10.1073/pnas.1410800111
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency calcium oscillations accompany deoxyhemoglobin oscillations in rat somatosensory cortex

Abstract: Spontaneous low-frequency oscillations (LFOs) of blood-oxygenlevel-dependent (BOLD) signals are used to map brain functional connectivity with functional MRI, but their source is not well understood. Here we used optical imaging to assess whether LFOs from vascular signals covary with oscillatory intracellular calcium (Ca 2+ i ) and with local field potentials in the rat's somatosensory cortex. We observed that the frequency of Ca 2+ i oscillations in tissue (∼0.07 Hz) was similar to the LFOs of deoxyhemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 55 publications
4
46
0
Order By: Relevance
“…The local field potential (LFP) from the superficial layers is measured across the windowed region of cortex (Figure 2A). We choose to use the LFP as an aggregate measure of neuronal activity, as opposed to intracellular calcium signals (Du et al, 2014; Ma et al, 2016; Vanni et al, 2017), as a means to identify different frequency bands of neuronal activation and to connect our work with past neurovascular studies (Keller et al, 2013; Lachaux et al, 2007; Niessing et al, 2005; Nir et al, 2007; Nir et al, 2008; Thompson et al, 2013). We also were cautious of potential ictal events in mice bred to express intracellular calcium reporters (Steinmetz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The local field potential (LFP) from the superficial layers is measured across the windowed region of cortex (Figure 2A). We choose to use the LFP as an aggregate measure of neuronal activity, as opposed to intracellular calcium signals (Du et al, 2014; Ma et al, 2016; Vanni et al, 2017), as a means to identify different frequency bands of neuronal activation and to connect our work with past neurovascular studies (Keller et al, 2013; Lachaux et al, 2007; Niessing et al, 2005; Nir et al, 2007; Nir et al, 2008; Thompson et al, 2013). We also were cautious of potential ictal events in mice bred to express intracellular calcium reporters (Steinmetz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These low frequency signal fluctuations, in different regions of the brain, can be synchronized or temporally correlated (Biswal et al, 2010; Di et al, 2013; Du et al, 2014). This synchronized activity reflects functionally connected brain regions or networks.…”
Section: Neuroimaging Methodsmentioning
confidence: 99%
“…23 Inter- and intra-regional resting-state fMRI connectivity reflect synchronous oscillations in neuronal activity 2426 that are largely insensitive to vasodilation, 26 and are also unlikely to be affected by brain-wide changes in metabolic supply. Moreover, prior research has shown that measures of resting state functional connectivity are sensitive to effects of acute and chronic alcohol exposure on the brain.…”
Section: Introductionmentioning
confidence: 99%